Comparison of the use of neutrophil: lymphocyte count ratio (NLCR) to total leukocyte count in diagnosing appendicitis in adults with right iliac fossa pain - K.C., Rabindra; Bhattarai, Abhishek; Joshi, Rakshya; Kharel, Ashok; Iohani, Ishwar (Journal of Society of Surgeons of Nepal, 2018)
Introduction: Diagnosis of acute appendicitis (AA) is purely based on history, examination and few laboratory investigations. However, it is often a perplexing diagnostic problem during the early stages of the disease. Failure to make an early diagnosis is a primary reason for morbidity and mortality. Elevated leukocyte count is one of the indicators of appendiceal inflammation in patients with right iliac fossa pain and most of the patients with acute appendicitis present with leucocytosis. Recently, it has been seen that the neutrophil: lymphocyte count ratio (NLCR) is a more sensitive marker than leukocytosis in patients with acute appendicitis. Method: This is a prospective observational study conducted over a period of one year in the department of surgery at the Tribhuvan University Teaching Hospital, from September 2013 to August 2014. The clinical diagnosis of Acute appendicitis was made by history and clinical examinations and laboratory investigations. Total leukocyte count (TLC) and NLCR of patients diagnosed as AA were measured and recorded in the pro forma. Histological diagnosis was taken as the final diagnosis. Results: A total of 106 patients were included in the study. Two third of the patients were male. Right iliac fossa tenderness was the most common sign. Ultrasound was able to diagnose acute appendicitis in 40.65% of the cases. NLCR> 3.5 was observed in 90.56% of patients with acute appendicitis, whereas 78.3% of patients had leukocytosis only. High NLCR (5.60) is associated with complicated AA. Conclusion: NLCR is a more sensitive laboratory parameter than TLC in patients with RIF pain to diagnose acute appendicitis. A high NLCR ratio has a high likelihood of a complicated AA.